Perkembangan Kognitif Pada Anak Sekolah Dasar - Abd. Rahman Hakim Hasibuan; Abdi Maulana; Diha Stephenia Samosir; Syahrial Syahrial (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Cognitive development is an important aspect of children's growth, playing a crucial role in their ability to learn, think and solve problems. Children at elementary school age, who are approximately 6 to 12 years old, experience significant progress in their cognitive development. At this stage, they begin to develop abstract thinking skills, expand their vocabulary, and hone their problem-solving abilities. The literature review research methodology is a research approach that aims to investigate and synthesize relevant literature related to a particular topic. In this methodology, researchers collect, evaluate, and reconstruct information from various literary sources such as scientific journals, books, research reports, and other scientific articles. The primary goal of literature review research is to present a comprehensive understanding of an existing research topic, identify knowledge gaps, and provide a framework for further research. This theory covers the stages of children's cognitive development, including the concrete operations stage which often occurs in elementary school age children. The important role of teachers and a supportive learning environment in elementary schools is crucial in optimizing children's cognitive development. Apart from that, support from parents also plays an important role in providing appropriate stimulus and providing opportunities for children to explore their interests and talents.